2012
DOI: 10.1002/prep.201200108
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanate‐Free and Dual Curing of Smokeless Composite Rocket Propellants

Abstract: Traditional composite rocket propellants are cured by treatment of hydroxyl‐terminated prepolymers with polyfunctional aliphatic isocyanates. For development of smokeless composite propellants containing nitramines and/or ammonium dinitramide (ADN), energetic binder systems using glycidyl azide polymer (GAP) are of particular interest. Polyfunctional alkynes are potential isocyanate‐free curing agents for GAP through thermal azide‐alkyne cycloaddition and subsequent formation of triazole crosslinkages. Proparg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 21 publications
0
47
0
2
Order By: Relevance
“…Reed [9] focused exclusively on the curing reaction of azides with ethinyl compounds. Landsem [10] reported isocyanate-free curing of several smokeless composite rocket propellant formulations by using bisphenol A, bis(propargyl ether) and GAP binder. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 How Ghee Ang et al [11] suggested that with activated acetylenes, the curing takes place in the temperature range of 35-50 8C, which is suitable for processing of propellant formulations.…”
Section: Introductionmentioning
confidence: 91%
“…Reed [9] focused exclusively on the curing reaction of azides with ethinyl compounds. Landsem [10] reported isocyanate-free curing of several smokeless composite rocket propellant formulations by using bisphenol A, bis(propargyl ether) and GAP binder. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 How Ghee Ang et al [11] suggested that with activated acetylenes, the curing takes place in the temperature range of 35-50 8C, which is suitable for processing of propellant formulations.…”
Section: Introductionmentioning
confidence: 91%
“…Huisgen azide-alkyne cycloaddition (AAC) has been gradually studied as the most promising replacement of urethane reaction for elastomeric matrix of solid composite propellants [12,[15][16][17][18]. Nowadays, AAC reaction is similarly considered as the "click" reaction using metal catalysts such as copper (Cu) and ruthenium (Ru).…”
Section: Introductionmentioning
confidence: 99%
“…ADN has been strongly regarded as the most promising replacement of AP, which is widely used in solid rocket propellant and releases hydrogen chloride in combustion. Under urethane curing systems, which have been a long‐used technology in conventional solid propellants, ADN draws serious compatibility problems with isocyanate curing agents, resulting in evolving gaseous products during the curing reaction 8–11.…”
Section: Introductionmentioning
confidence: 99%